2025 Subject Index. (Journal of Occupational & Environmental Hygiene, 2025)
The article provides a comprehensive overview of various occupational health and safety topics, focusing on exposure assessments, risk management, and the implications of specific chemicals and materials in different work environments. Key subjects include the evaluation of airborne exposures to hazardous substances like asbestos and hexavalent chromium (CrVI), the impact of heat stress on agricultural and construction workers, and the effectiveness of personal protective equipment (PPE) in mitigating risks. Additionally, it discusses the role of occupational health professionals in addressing workplace violence and the importance of educational materials for hearing conservation in the U.S. Air Force. The article serves as a resource for understanding the complexities of occupational health and safety across diverse industries.